Different Concentrations Of Cassava Flour (Manihot utilisima) And Wheat Flour On The Physicochemistry And Organoleptic Quality Of High-Fiber Steamed Brownies - Kurnia Hartati, Fadjar; Gabriel Susanto, Nikolaus (Demeter: Journal of Farming and Agriculture, 2024)
At present, the level of public consumption of wheat flour is increasing but the production of wheat in Indonesia is very minimal so Indonesia still expects imports from several countries. Meanwhile, the use of low-fiber wheat flour can increase peoples consumption in excess, so it can increase excess calorie levels in the body which can trigger obesity. Therefore, it necessary to substitute local-based flour such as cassava flour to reduce wheat flour consumption and increase fiber content in the resulting product. This study aims to determine the effect of different concentrations of wheat flour and cassava flour and determine the right concentration on the chemical and organoleptic quality of steamed brownies as high fiber food. The research method used a a research design using a 1-factor Completely Randomized Design (CRD) with 4 treatments and 3 replications. Chemical quality analysis on steamed brownies, namely water content, crude fiber content, and calories. The organoleptic test is color, aroma, taste, and tenderness. The results showed that between different proportions of wheat flour and cassava flour had a significant effect on crude fiber content and very significant effect on calorie content. Based on the determination of all research parameters, it shows that formulation 3 with 60 grams wheat flour and 40 grams cassava flour is the best treatment with a result value (NH) 0.692 with parameter criteria in the form crude fiber content 22.9%, calorie content 6.74 cal, moisture content 19.04%, tenderness 3.68 (like), color 3.96 (like), taste 3.78 (like), and aroma 3.89 (like).